ON RECURSIVELY DIFFERENTIABLE QUASIGROUPS - Larionova-Cojocaru, Inga (My University, 2015)
If ( ),Q ⋅ is a binary groupoid then will denote its recursive derivative of order s by „ s ⋅ ”, hence 0 1 2 1 , , , ( ) ( ), s s s x y x y x y y xy x y x y x y − − ⋅ = ⋅ ⋅ = ⋅ ⋅ = ⋅ ⋅ ⋅K for every , .x y Q∈ If the recursive derivatives „ s ⋅ ”, s=1,2,…,k, of a binary quasigroup ( ),Q ⋅ are quasigroup operations, then ( ),Q ⋅ is called recursively k- differentiable. The notions of recursive derivatives and recursively differentiable quasigroups raised in the algebraic coding theory [1]. Recursively differentiable binary quasigroups in particular groups, are studied in the present paper. Proposition 1. If a quasigroup ( ),Q ⋅ , with the left unit, is recursively 1- differentiable then the mapping 2 x x→ is a bijection. Proposition 2. A diassociative loop ( ),Q ⋅ is recursively 1-differentiable if and only if the mapping 2 x x→ is a bijection. Corollary 1. A Moufang loop ( ),Q ⋅ , in particular a group, is recursively 1- differentiable if and only if the mapping 2 x x→ is a bijection on Q . Corollary 2. Finite groups of even order are not recursively 1-differentiable.
LARIONOVA, Inga. On recursively differentiable quasigroups. In: Tendinţe contemporane ale dezvoltării ştiinţei: viziuni ale tinerilor cercetători: conferința științifică internațională a doctoranzilor, 10 martie 2015, Chișinău. Chișinău: Artpoligraf, 2015, p. 21.